LSM DAN GERAKAN ANTI KORUPSI : ANALISIS PERAN LSM DALAM MEMBANGUN KESADARAN ANTI KORUPSI DAN DALAM MEMERANGI TINDAK PIDANA KORUPSI DI KOTA SEMARANG - Puji Astuti (Faculty of Social and Political Sciences, Universitas Diponegoro, 2014)
Corruption in Indonesia still be a great challenges, because corruption more extend, not only in national government, but also expand in local government, mainly after local election choose by people. Almost local government should facing corruption that involved almost all institution, not only in legislative, excecutive, and judicative, but also private corporation. Thus research would describe corruption in Semarang City, and how the role of NGO, mainly Pattiro and KP2KKN in combating corruption. NGO have an important role both in educating of Anti-Corruption and controlling the handle of corruption. The most goals of Education to the people mainly how people being intolerance to corruption. Education program involving other institution like KPK, ICW and other NGO with the same of vision in combating corruption. In other side, the role of NGO was cotrolling judicature process with Mass Media as a partner. Without Mass Media, NGO won’t be an effectiveness in combating corruption. Because NGO still facing lack of resources in Human and financial as a force in combating corruption, so making a coorporation with University would be the best choices in the future, mainly in anti-corruption education.